The Influence of Perceived Organizational Support on Contextual Performance Mediated by Job Satisfaction among Textile Industry Employees in Yogyakarta - Noviza, Neza; Aulia, Aulia (Universitas Mercu Buana Yogyakarta, 2025)
Employees with low contextual performance often struggle to adapt and will experience difficulty in facing changes or new challenges in the work environment. This research examines the influence of perceived organizational support on contextual performance, with job satisfaction as a mediator. A quantitative approach utilizing multivariate methods was employed in this study. The population consisted of employees working in the textile industry in Yogyakarta. The sampling technique used was purposive quota sampling, resulting in 385 samples. The measurement tools included scales for contextual performance, job satisfaction, and perceived organizational support, with data collection conducted via Google Forms. Data analysis was performed using path analysis techniques with the help of Partial Least Squares (PLS). The analysis results revealed a path coefficient of 0.706 and a p-value of 0.000 (p<0.01). Therefore, it can be concluded that job satisfaction mediates the relationship between perceived organizational support and contextual performance. Additionally, there is a highly significant influence of perceived organizational support on contextual performance, a significant influence of perceived organizational support on job satisfaction, and a substantial impact of job satisfaction on the contextual performance of textile industry employees in Yogyakarta.